Representation Of Tourism Product Attributes And Visit Intention Through Electronic Word Of Mouth: A Content Analysis Of Tourist Reviews Of Holbung Hill, Samosir - Ruth Letare Nur Cahaya Lumbanraja; Amrin Mulia U. Nasution (Universitas Dehasen Bengkulu, 2026)
Holbung Hill is one of the leading nature-based tourism destinations in Samosir Regency that has gained increasing exposure through tourists’ online reviews. This study aims to analyze the tourism product attributes represented in online tourist reviews and to identify how electronic word of mouth (e-WOM) reflects tourists’ visit intention. A qualitative approach with content analysis was employed using 120 tourist reviews collected from Tripadvisor and AllTrails between January and June 2026. The data were analyzed through data reduction, thematic coding, categorization, data display, and conclusion drawing. The findings reveal that natural attraction is the most dominant tourism product attribute, particularly the panoramic view of Lake Toba and the surrounding green hills, which constitute the destination’s primary competitive advantage. In contrast, amenities and accessibility remain the main weaknesses, as reflected in recurring complaints regarding the limited availability of sanitation facilities, insufficient supporting infrastructure, and slippery hiking trails during the rainy season. Furthermore, the analysis indicates a shift in the role of e-WOM, from providing practical travel information (informational warning) to serving as a promotional medium (promotional recommendation) that encourages potential visitors to visit the destination. Despite several negative reviews concerning facilities, visit intention is predominantly represented by tourists’ willingness to recommend the destination and their intention to revisit. These findings suggest that the outstanding natural attractions compensate for the limitations of amenities, thereby fostering positive perceptions and strengthening tourists’ visit intention toward Holbung Hill.